Metodologias ativas offline e online na formação de professores para a educação profissional e tecnológica: trilhando os caminhos das MAPAs - Ferreira, Mariana Dalcin (2022)
The present study, linked to the line of research Management of Networked Educational Technologies, of the Graduate Program in Networked Educational Technologies at UFSM – RS, addresses educational spaces and teaching-learning methods as they have become more active and reactive to keep up with changes in the contemporary world. These changes make us think that the integration of technologies and Active Methodologies can contribute to the training of students in a Special Teacher Training Program for Professional Education (PEG), bachelors and future education professionals, who, in turn, will be able to adapt to customize their educational practices according to the scientific specificities of the area of origin. Thus, from questions and reflections, we honed the main objective of the research, that is, to analyze to what extent the Active Methodologies can be combined with digital resources, in teacher training workshops for Professional and Technological Education, for possible online customizations and offline. With a qualitative and quantitative approach and procedures based on action research, seven models of Active Methodologies for the Personalization of Learning, the MAPAs, were developed and implemented, enabling proposals for offline and online activities. The workshops on Jornal Falado, Brainstorming, Simulated Jury, Discovery and Investigation, Dramatization, Conceptual Maps and Quiz made it possible to collect and record information for analysis. The Diagnostic Questionnaire, Proposed Activities, Assertive Questionnaire about the workshops, Rubric and Final Questionnaire constituted the data collection instruments. The results showed the relevance of using Active Methodologies and Digital Educational Resources as an innovative possibility in different contexts and educational spaces, such as EPT, as well as the importance of pedagogical intentionality when making use of these strategies, aiming to contemplate both the curriculum to students' needs and aptitudes. In addition, it was noticed that the methodologies whose implementations are more practical, obtained better evaluations than the proposals that aimed to enhance, with greater depth, the development of cognitive learning, consequently, required greater efforts for the elaboration and implementation. Therefore, it is concluded that the use of developed models (MAPAs) for a teacher training course can indeed provide the expansion of students' knowledge, as they provide the possibility of adaptation/personalization for different areas of knowledge, enhancing teaching practices of bachelors who seek the course (PEG) for pedagogical qualification, so necessary to work in the world of work in the field of education.